Index Value of Goat Feed Based In Sacco and In Vivo Study - Rasjid, Syamsuddin; Ismartoyo, . (Buletin Nutrisi dan Makanan Ternak, 2014)
The objective of this study was to measure the degradation characteristics of feed (in sacco), feed intake and digestibility (in vivo), and determining the index value of 4 types of goats feed (T1 = elephant grass, grass field = T2, T3 = grass kolonjono, T4 = mango leaves). Research in sacco and in vivo requires 4 goats. Each feed (4 replicates) will be incubated for 8, 12, 24, 48, 72, and 96 hours, into the rumen of goats. All types of feed are given to the goats were divided into 4 treatment feed. Each goat was given one type of feed. In vivo data were analyzed using a completely randomized experimental design, followed by Duncans test (Steel and Torrie, 1980). Observations intake and digestibility of feed, then predicted from degradation characteristics of feed (in sacco) using multiple-regression analysis. From the regression equation can be further specified index value of feed (Ãrskov et al, 1988; Kibon and Ãrskov, 1993; Khazal et al, 1992; Shem et al, 1995; Fertile et al, 1999). The best results of In Vivo digestibility is elephant grass, followed by mango leaves feed, kolonjono grass and field grass. Weight gaint generally do not show significant differences. These results indicate that the index values of goats feed varies between one to the other feeds.Â